Design and simulation of a highly efficient eco-friendly, non-toxic perovskite solar cell - G. S. Ahathiyan; H. Victor Du John; D. Jackuline Moni; K. Martin Sagayam; Binay Kumar Pandey; Digvijay Pandey; Mesfin Esayas Lelisho (Discover Nano)
Abstract A highly efficient and nontoxic material methylammoniumtin(II) iodideperovskite solar cell is proposed. This proposed solar cell uses CH3NH3SnI3 as the absorber layer, TiO2 as an Electron transport layer (ETL), Indium tin oxide as a buffer layer, and Copper(I) oxide as the hole transport layer (HTL). The device is simulated using the SCAPS-1D simulation tool. This study details the optimization of a set of parameters, including the defect densities and the thickness of the absorber layer. The proposed structure is highly optimized result of 31.73% of enhanced power conversion efficiency (PCE), a JSC of 24.526 mA/cm2 (short-circuit current), FF of 81.40% (fill factor), and a VOC of 1.56 V (open-circuit voltage) is obtained through simulation process. Compared to previously reported works, the performance of the device has improved significantly due to better optimization. Along with this electrical characteristic temperature analyses, conductance voltage, capacitance–voltage, and bandgap analyses have also been carried out to examine the device’s efficiency and performance.